Is the Iloilo river estuary still a nursery ground for important marine fishery resources during the Northeast monsoon?. - Roth, Alexander James W. (Miag-ao, Iloilo University of the Philippines Visayas, 2018)
Ichthyoplankton and decapod larvae parameters were analyzed and correlated with environmental conditions to assess if Iloilo River Estuary is still a nursery ground for economically important marine fishery resources during the Northeast Monsoon. The sampling was conducted during the first and third quarter moon by towing a conical plankton net in three stations, namely the upstream, upper midstream and lower midstream. A total of 7 taxonomic groups of ichthyoplankton and 7 decapod larvae taxa were recorded in densities ranging from 70.8 to 404.2 ind./100m3 and 112.7 to 1277.6 ind./100m3 for ichthyoplankton and decapod larvae, respectively. Ichthyoplankton samples in all three zones were dominated by Gobiidae larvae (>70% relative abundance), while Sesarmidae and Dotillidae dominated decapod larvae samples in all three zones (.65%). Ichthyoplankton and decapod larvae frequency of occurrence ranged from 0.44 to 0.49 and 0.65 to 0.84, respectively. Strong positive correlations were discovered between larger mangrove cover and higher dissolved oxygen concentrations with higher larvae taxonomic diversity and density. Ammonia concentrations were high enough in all three zoes to be toxic to ichthyoplankton and decapod larvae. Fewer taxa and similar densities were sampled in Iloilo River when compared to other estuarine nursery grounds. This implies Iloilo River is still a nursery ground, but is utilized by very few taxa during the Northeast Monsoon Clupeidae was the only economically important ichthyoplankton sampled; though it is unlikely this taxonomic group utilizes the estuary as a nursery ground. Portunidae, Penaeidae, and Palaemonidae were the only economically important taxa utilizing the estuary as a nursery ground. Based on this information, further research exploring how to improve the ecological condition of the estuary should be conducted to hopefully increase the number of economically important taxa.
Thesis (M. S. Fisheries-Fisheries Biology) -- Miagao, Iloilo : University of the Philippines Visayas, June 2018.ne 2018.